Marcadores inflamatórios solúveis como preditores de alteraçõeshistologicas hepáticas e resposta terapêutica na infecção crônica pelovírus da hepatite C - Alexandre Sampaio Moura (2008)
Host immune response seems to be responsible for progression of liver disease among patients chronically infected with hepatitis C virus (HCV), but is also crucial for successful clearance of the virus following specific therapy. Activation of the immune system involves the release of cytokines and their receptors that can be measured in plasmatic samples. The present study aimed to evaluate the association betweenchemokines and soluble tumor necrosis factor receptors (sTNFR) plasmatic levels and both liver histological changes and therapeutic response to interferon-¿ and ribavirin. From June 2005 to December 2007, 73 treatment-naive patients, chronically infected with HCV andwith an available liver biopsy fragment were included in the study. Socio-demographic, clinical and laboratory data were collected and plasmatic levels were assessed for CCL2, CCL3, CCL11, CCL24, CXCL9, CXCL10, sTNFR1 e sTNFR2. Histological findings of the liver fragment were reviewed and classified according to the METAVIR scoringsystem and stratified as following: A . 1 (none or mild inflammatory activity) e A.2 (moderate or severe inflammatory activity); F.1 (none or mild fibrosis) e F.2 (moderate or sever fibrosis). Plasmatic levels of CXCL9, sTNFR1 and sTNFR2 were significantly associated with liver fibrosis with higher median levels among those with moderate/severe fibrosis if compared to those with no or mild fibrosis (p=0,014; p=0,012; p=0,009,respectively). Plasmatic sTNFR2 levels were significantly associated with liver necroinflammatory activity with higher median leves among those with moderate/severe activity if compared to those with no or mild activity (2,34 ng/mL vs. 1,99 ng/mL; p=0,019). Forty one patients were treated with interferon-¿ and ribavirin during the study period and the association between the levels of these inflammatory markers and therapeutic response was analyzed. Pre-treatment CXCL10 levels were significantly higher among patients without early or sustained virologic response if compared to non-reponders (512,9 pg/mL vs 179,1 pg/mL; p=0,011 and 289,9 pg/mL vs. 142,7 pg/mL; p=0,045, respectively). Accuracy of CXCL10 as predictor of absence of EVR and SVR was 0,79 (CI95%: 0,59-0,99) and 0,69 (CI95%: 0,51 - 0,87), respectively. In conclusion, plasmatic leves of CXCL9, sTNFR1 and sTNFR2 were independetly associated with liver histological changes suggesting a role of TNF activation and Th1-type cell-mediated immune response in the pathogenesis of HCV infection. In addition, pre-treatment CXCL10 levels were predictor of both early and sustained virologic response to interferon-¿ and ribavirin and might be potentially useful in the evaluation of candidates for therapy.